PERBEDAANEFEKTIFITASMENGUNYAH PERMEN KARET RENDAH GULA DAN MENGULUM GRAPEICE CUBETERHADAP RASA HAUS PADA PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISIS - Asmira Dewi; Sofiana Nurchayati; Jumaini Jumaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Thirs is the general condition that have been in patient undergoing hemodyalisis causedby decrease secretion of saliva.The purpose of this research is to know effectiveness of chewing bubble gum and suck grape ice cube against thirst forpatient chronic kidney disease that undergoing hemodialysis that has been done at RSUD Arifin Ahmad Riau Province.The design of this research is quantative research with quasy eksperiment and pre test – post test design with twocomparisons approach with 34 respondents that taken by inclusion criteria that use purposive sampling technic. Theinstruments that use in this research is Visual Analogy Scale. The analysis in this research is bivariate that useWilcoxon and Mann-Whitney test. The result showed difference of average thirst score after and before chewing bubblegum with p value 0.029 > α (0.05). Difference of thirst score average after and before suck grape ice have p value0.000 < α (0.05). Difference of thirst score average on chewing bubble gum group and suck grape ice cube after givenintervention have p value 0.116 > α (0.05), that showed there is no difference average thirst score of chewing bubblegum and suck grape ice cube for patient chronic kidney disease that undergoing hemodialysis.Keyword: Chewing bubble gum, Chronic kidney disease, Suck grape ice cube, Thirst